Never walk alone: achieving work performance through networking ability and autonomy. Issue 2 (13th February 2017) - Nesheim, Torstein; Olsen, Karen Modesta; Sandvik, Alexander Madsen
Abstract : Purpose: The purpose of this paper is to examine the association between networking ability, autonomy and work performance. Design/methodology/approach: The data, collected from a sample of 510 employees in a professional service firm, were analysed using regression analysis. Findings: First, networking ability and autonomy are positively associated with in-role and extra-role performance. Second, the greater the job autonomy, the stronger the effect of networking ability on in-role performance. Originality/value: This paper adds to the growing body of literature on demand for social and interpersonal skills in organisations. The authors combine the literature on work design with the literature on networking ability and complexity in employment relations. The authors' findings show the importance of networking ability and autonomy for work performance, as well as pointing to factors such as age and work experience.